Analisis Pembangkit Listrik Tenaga Biogas Berbasis Konsep Green Technology Studi Kasus di Desa Puter Kembangbahu - Nahdia Rupawanti BR; M Iqbal Syauqi (Jurnal JE-UNISLA : Electronic Control, Telecomunication, Computer Information and Power System, 2018)
This research is based on the exploration of renewable energy utilization by utilizing the potential of cow livestock waste in cattle farm area as a raw material of biogas energy using the green technology concept. The results of this research show that: (1) the performance of  biogas power plant with 115 cattle population producting: 25 kg/day cow waste for each cow in average, 2.857 kg/day cow waste in average for the total population, biogas potency 23 m3/day, methane potency 12,006874 m3/day, total solid 4,83 kg/cow/day, total solid percentage 0,168 %, volatile solid 437 kg/day, and volatile solid percentage 0,152 %, (2) The efficiency of biogas power plant potency of 23 m3/day can be converted into the generated electric energy equal to 1,0005 KWh, 220 W of power flame within 5 hours. Therefore, the power generated from biogas power plant is 1 KWh.